Multicenter study: carotid endarterectomy in the first hours after ischemic stroke - A. N. Kazantsev; R. A. Vinogradov; M. A. Chernyavsky; V. N. Kravchuk; V. V. Matusevich; K. P. Chernykh; A. R. Shabaev; I. N. Shukurov; G. Sh. Bagdavadze; V. A. Lutsenko; R. V. Sultanov; E. F. Vaiman; et al. (Российский кардиологический журнал, 2021)
Aim. To analyze inhospital outcomes of carotid endarterectomy (CE) in the acute period (within 3 days from the onset) of ischemic stroke.Material and methods. This retrospective multicenter study for the period from January 2008 to August 2020 included 357 patients who underwent CE in the acute period of stroke. An interdisciplinary commission defined the revascularization timing. There were following inclusion criteria: 1. Mild neurological disorders: NIHSS stroke of 3-8; modified Rankin Scale score <2; Bartel index >61; 2. Indications for CE according to the current national guidelines; 3. Brain ischemic focus <2,5 cm in diameter. There were following exclusion criteria: 1. Presence of contraindications to CE. The endpoints were such unfavorable cardiovascular events as death, myocardial infarction (MI), stroke/transient ischemic attack (TIA), silent stroke, silent hemorrhagic transformations, Bleeding Academic Research Consortium (BARC) type >3b bleeding, internal carotid artery thrombosis, composite endpoint (death + all strokes/TIA + MI). Silent strokes were those strokes, established according to control multi-slice computed tomography angiography, without symptoms.Results. During the in-hospital follow-up period, 8 deaths (2,24%), 5 MIs (1,4%), 6 strokes/TIAs (1,7%), 15 silent ischemic strokes (4,2%), 13 hemorrhagic transformations (3,6%), 26 silent hemorrhagic transformations (7,3%), and 6 BARC type >3b bleeding (1,7%) were recorded. Thus, the combined endpoint was 20,4% (n=73).Conclusion. Due to the high incidence of cardiovascular events, CE is not a safe operation for patients in the acute period of ischemic stroke. The stroke + mortality rate exceeding 3% demonstrates the ineffectiveness of this method of treatment.